Sustainable leadership : lessons of vision, courage, and grit from the CEOs who dared to build a better world - Murphy, Clarke (Ascent Audio, 2022)
Deliver extraordinary sustainability results for your business In Sustainable Leadership: Lessons of Vision, Courage, and Grit from the CEOs Who Dared to Build a Better World, accomplished leadership expert Clarke Murphy shares a can't-miss toolkit for delivering remarkable sustainability results. You'll learn what it takes to become a sustainable leader and how you can turn your sustainability promises into tangible action on the ground. Drawing on the real-life stories of sustainable leaders from across the world, Murphy proves that sustainability success is within reach for every business executive. He debunks the myth that sustainability is at odds with profitability and reveals the inside track on how to make sustainability your new growth strategy. You'll find: a step-by-step framework on how to build your sustainable leadership legacy; pragmatic examples of balancing the demands of shareholders and other stakeholders; lessons from CEOs on how they stayed the course in the face of setbacks; and strategies to prepare your up-and-coming executives to carry the sustainability mantle and help you hit your short and long-term sustainability goals.